Elasto-plastic response of bridge piers due to vehicle collision-a static approach - Joshi, A.S.; Gupta, L.M. (Journal of Structural Engineering, 2025)
Due to non-availability of space, in cities, for road widening, traffic is being vertically graded. Flyover is a very common option available today. Due to heavy traffic conditions coupled with lesser space, authorities are unable to provide enough setbacks around the piers subjecting the structure to the hazard of a vehicle collision. The present work is aimed at a study of the provisions in the specifi cations of a few countries on a common platform related to vehicle collision on piers. The specifications are also investigated in the light of collision forces obtained by vehicle simulation from past research work. A Finite Element Analysis is carried out considering the force due collision as a static force. Elasto-Plastic responses of solid wall type, solid and hollow circular piers are studied and consequent reduction in stiffness, post collision, is envisaged.